PK11195 Protects From Cell Death Only When Applied During Reperfusion: Succinate-Mediated Mechanism of Action - Seidlmayer, Lea K.; Hanson, Benjamin J.; Thai, Phung N.; Schaefer, Saul; Bers, Donald M.; Dedkova, Elena N. (Frontiers in Physiology, 2021)
Aim: Reperfusion after myocardial ischemia causes cellular injury, in part due to changes in mitochondrial Ca2+ handling, oxidative stress and myocyte energetics. We have previously shown that the 18-kDa translocator protein of the outer mitochondrial membrane (TSPO) can modulate Ca2+ handling. Here, we aim to evaluate the role of the TSPO in ischemia/reperfusion (I/R) injury. Methods: Rabbit ventricular myocytes underwent simulated acute ischemia (20 min) and reperfusion (at 15 min, 1 and 3 hours) in the absence and presence of 50 µM PK11195, a TSPO inhibitor. Cell death was measured by LDH assay, while changes in mitochondrial Ca2+, membrane potential (m) and reactive oxygen species (ROS) generation were monitored using confocal microscopy in combination with fluorescent indicators. Substrate utilization was measured with Biolog mitochondrial plates. Results: Cell death was increased by 200% following I/R compared to control untreated ventricular myocytes. Incubation with 50 µM PK11195 during both ischemia and reperfusion did not reduce cell death but increased mitochondrial Ca2+ uptake and ROS generation. However, application of 50 µM PK11195 only at the onset and during reperfusion effectively protected against cell death. The large-scale oscillations in m observed after 1h of reperfusion were significantly delayed by 1 µM cyclosporin A and almost completely prevented by 50 µM PK11195 applied during 3 hours of reperfusion. After an initial increase, mitochondrial Ca2+, measured with Myticam, rapidly declined during 3 hours of reperfusion after the initial transient increase. This decline was prevented by application of PK11195 at the onset and during reperfusion. PK11195 prevented a significant increase in succinate utilization following I/R and succinate-induced forward-mode ROS generation. Treatment with PK11195 was also associated with a significant increase in glutamate and a decrease in leucine utilization. Conclusion: PK11195 administered specifically at the moment of reperfusion limited ROS-induced ROS release and cell death, likely in part, by a shift from succinate to glutamate utilization. These data demonstrate a unique mechanism to limit cardiac injury after I/R.